KEDUDUKAN BANK INDONESIA DALAM HAL KEPAILITAN BANK DITINJAU DARI UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN BANK DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Irwan Mahardika, Gede; Dunia, Ngakan Ketut; Rudy, Dewa Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
Construction law on bankruptcy of a bank that is in Bankruptcy Act fully authorizes Bank Indonesia to file for bankruptcy on a bank is not in line with the stages and processes in general insolvency giving sovereignty to the creditor on the basis of the relationship existing debts in making Commercial debtors in bankruptcy court. Results of research conducted in the field Showed that the position of Bank Indonesia as the banking authorities as the only party that can file for bankruptcy on a bank is not in accordance with the principles of the general bankruptcy protection for the rights and interests of creditors. BI Position as the only party authorized to make insolvent banks Because if the bank can Easily be filed by any creditor bankruptcy then the risk is very high, Because of the simple setting of the bank's bankruptcy would result in public confidence in the bank could be lost.
Keywords: Bankruptcy, Bank of Indonesia